THE ROLES OF EXTERNAL FACTORS IN LIAM O’NEILL’S PURSUIT OF IDENTITY AS A TRANSGENDER YOUTH IN JULIE ANNE PETERS’ LUNA - AULIA, MIKY ZAHRATUL (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: transgender, social psychology, interpersonal relationship, groupdynamics   Transgender is the term that is used to describe someone with different gender behavior from their actual gender. Nowadays, there are some phenomena in which a transgender has come out in juvenile age that is called as transgender youth. A transgender usually tends to not reveal his identity due to the social opinion toward transgender as a social problem. This study focuses on the role of external factors toward transgender youth in Luna by Julie Anne Peters which shows the influence of society toward transgender in the process of coming out. The story depicts the life of a transgender youth, Liam who tries to come out in public with help from people around him. This study aims to reveal the role of people around Liam in helping him find his identity as a transgender youth. Social psychology approach is used to analyze the role of people around Liam that influence his thought and behavior with interpersonal relationship, group dynamics. In addition, Transgender Identity Affirmation and Mental Health theory by Nuttbrock, Rosen blum and Blumenstein is used to support the analysis.The study findings reveal that there are two external factors which influence Liam’s behavior and thinking in the process of coming out. They are family and affiliation. They have significant influences to his behavior in making him confident in facing his life as a transgender.Liam’s process of coming out as a transgender is influenced by the acceptance from his surroundings. When the surroundings accept his come out process, it actually becomes the significant support for a transgender. In fact, that acceptance has a correlation with his mental health as shown in this study. For future research the writer suggests that the English Department students do research on transgender-themed literature by using Devor’s Transgender Identity model that describes fourteen processes of transgender identity development. The writer hopes that doing this study can raise the awareness of the existence of transgender, particularly the young people’s.